T3 THYROTOXICOSIS SECONDARY TO GRAVES DISEASE EXHIBITING RESISTANCE TO RADIOACTIVE IODINE-131 THERAPY - Mohamad, Aimi Fadilah; Shah, Fatimah Zaherah Mohamed; Zainordin, Nur Aisyah; Warman, Nur’aini Eddy; Hatta, harifah Faradila Wan Muhammad; Awang, Mohd Hazriq; Ghani, Rohana Abdul (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Radioactive Iodine (RAI) therapy with Iodine-131 is commonly used as definitive therapy for Graves’ Disease. It is especially useful when there is poor response to anti-thyroid medications. The failure rate for RAI therapy is approximately 15% and known predictors for failure are RAI doses of <13 mCi and prior methimazole therapy. Initial free T3 (fT3) and T4 (fT4) levels at presentation may also predict response to RAI therapy. CASE We present a case of a 44-year-old female with Graves’ Disease and persistently elevated fT3 levels. Her main symptoms were weight loss, palpitations and severe panic and anxiety attacks. She had mild ophthalmopathy and a moderate goitre but no compression symptoms. She was treated with carbimazole for 2 years but was unable to achieve euthyroidism. Her initial thyroid function tests showed TSH <0.01 mIu/L (NR: 0.27 – 4.2), fT4 >100 pmol/L (NR: 12 - 22) and fT3 >50 pmol/L (NR: 3.5 - 6.5). Thyroid peroxidase (TPO) antibodies were elevated at 692 IU/ml (NR <35). With carbimazole, her fT4 normalized (range: 13 - 19) but fT3 remained elevated (range: 8 - 13). Carbimazole dose was increased and fT3 normalized to 5.1 pmol/L but fT4 decreased to 1.7 pmol/L. Her TSH remained suppressed throughout. She received RAI at 20 mCi with immediate relapse after 4 weeks (fT4 >100). Eight months later, she had second RAI with 20 mCi but remained hyperthyroid within 6 months of follow-up. CONCLUSION Despite a total RAI dose of 40MCi, her Graves’ Disease remained active and thyroidectomy would be the next option. Her resistance to RAI may be related to her predominant pattern of elevated fT3 levels. The mechanism of this is unclear but may be related to impaired RAI uptake by the thyroid gland. Future studies may be useful to evaluate this further.